Determinants of internal audit function on emerging markets: SEM-PLS approach - Ahmad Subaki; Rachmawati Rachmawati; Wahyu Widarjo; Djuminah Djuminah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The existence of an internal audit function (IAF) is very important to describe companies that follow the criteria of good corporate governance, so it needs to be investigated further because there is still a lack of research that discusses IAF. This research is a quantitative study using secondary data in the form of company annual reports included in LQ45 on the Indonesia Stock Exchange. Data processing is carried out with a different approach using SEM-PLS. The purpose of this study was to determine the effect of internal and external risk management on the internal audit function. So, from our findings, it can be concluded that the level of internal risk, external agency risk, and corporate governance is not significant to the internal audit function (IAF).